Acoustically assessed influence of air pore structure on failure of self-compacting concretes under compression - Gorzelańczyk, Tomasz (Journal of Civil Engineering and Management, 2012)
The paper presents the results of investigations into the influence of pore structure on the failure of self-compacting concretes modified with superplasticizers commonly used in construction. Pore structure examinations were carried out in practically the whole range of pore diameters by means of an image analyzer and a mercury porosimeter. The failure of the self-compacting concretes under compression, was investigated by the acoustic emission technique and other methods. The levels of cracking initiating stress σiand critical stress σcr, demarcating the different stages in the failure process, were determined. It has been shown that there is a relationship between the pore structure parameters and the levels. The fatigue strength of the self-compacting concretes was calculated from the experimental results and on this basis the suitability of the concretes for structures subject to cyclic loads was determined. Akustiškai įvertinta oro porų struktūros įtaka susitankinančio betono susilpnėjimui veikiant gniuždymui Santrauka. Straipsnyje pateikiami porų struktūros įtakos susitankinančio betono su superplastikliais susilpnėjimui tyrimų rezultatai. Buvo atlikti praktiškai visų skersmenų porų struktūros tyrimai naudojant vaizdo analizatorių ir gyvsidabrio porosimetrą. Susitankinančio betono susilpnėjimas esant gniuždymui buvo tiriamas akustinės emisijos ir kitais metodais. Nustatyti pleišėjimo lygiai ir įtampos, žymintys skirtingus susilpnėjimo lygius. Parodyta, kad yra ryšys tarp porų struktūros parametrų ir susilpnėjimo lygių. Pagal eksperimentinius rezultatus suskaičiuotas betono atsparumas ir nustatytas betono tinkamumas konstrukcijoms, atsižvelgiant į ciklines apkrovas. Reikšminiai žodžiai: susitankinantis betonas, porų struktūra, susilpnėjimas, gniuždymas, akustinė emisija, ultragarsai.